The busy leader's handbook : how to lead people and places that thrive - Studer, Quint (Wiley, 2020)
"After spending the last 30 years helping organizations and leaders reach peak performance, Quint Studer has pulled together his best practices, tools, tips and tactics for engaging employees, revitalizing cultures, and creating high performance companies. All his tactics and tools are easy to understand and implement. It will be comprehensive and will cover things like change management, leadership, communication styles, employee training and engagement, team building, as well as manager must haves like how to attract and retain talent, how to run a meeting, how to deal with low performers, how to have difficult conversations, and much more. This book will function almost as a desk reference/pocket guide. All chapters are written as "standalones." Busy managers/leaders can look at the Table of Contents, find a challenge they're facing, and instantly access "how to" advice they can put into practice right away"--